The Practical Problem With Carbapenem Testing and Reporting Accurate Bacterial Susceptibilities - Redell, Mark; Tillotson, Glenn S. (Frontiers in Pharmacology, 2022)
Background: Antibiotic resistance is an evolving issue which requires constant review. Susceptibility breakpoints are revised in line with new microbiological and pharmacological data. Susceptibility breakpoints for carbapenems and Enterobacterales were revised in response to the rise in resistance and the potential for standard doses of carbapenems to provide the necessary antibiotic exposure and to accurately identify rates of carbapenem resistance. Objectives: This review sought to identify real-world implications associated with lack of testing and reporting current carbapenem breakpoints and potential barriers that may impede implementation of these strategies. Methods: A literature review was conducted using PubMed and Google Scholar electronic databases. Results: The failure to adopt revised breakpoints incurs negative clinical outcomes and carries increased cost implications. However, there were several impediments highlighted which are barriers for laboratories to implement breakpoint updates. Conclusions: Possible practical steps to implement revised breakpoints which apply to carbapenems and Enterobacterales are proposed. The challenge for laboratories is to be aware and implement these changes to provide accurate and relevant susceptibility results for clinicians.